Antigen–antibody complex density and antibody-induced HLA protein unfolding influence Fc-mediated antibody effector function - Murali, Tanusya Murali; Gu, Yue; Minhat, Rabiatul Adawiyah; Yap, Jiawei; Wood, Kathryn J.; Wang, Cheng-I; Gascoigne, Nicholas R. J.; Anantharaman, Vathsala; MacAry, Paul Anthony (Frontiers in Immunology, 2024)
Donor-specific antibodies (DSAs) targeting mismatched human leukocyte antigen (HLA) molecules are one of the principal threats to long-term graft survival in solid organ transplantation. However, many patients with long-term circulating DSAs do not manifest rejection responses, suggesting a degree of heterogeneity in their pathogenicity and related functional activity. Immunologic risk stratification of transplant recipients is complicated by challenges intrinsic to defining alloantibody responses that are potentially pathogenic versus those that are not. Thus, a comprehensive understanding of how human alloantibodies target and interact with donor HLA molecules is vital for the development and evaluation of new strategies aimed at reducing antibody-mediated rejection responses. In this study, we employ hydrogen–deuterium exchange–mass spectrometry (HDX–MS), molecular dynamics (MD) simulations, and advanced biochemical and biophysical methodologies to thoroughly characterize a panel of human monoclonal alloantibodies and define the influence of Fc-region biology, antibody binding kinetics, target antigen density, and structural characteristics on their ability to potentiate the forms of immune effector mechanisms that are strongly implicated in transplant rejection. Our findings have significant implications for our understanding of the key biological determinants that underlie the pathogenicity or lack thereof of human alloantibodies.